2016
DOI: 10.3390/min6020050
|View full text |Cite
|
Sign up to set email alerts
|

Leaching Behavior and Potential Environmental Effects of Trace Elements in Coal Gangue of an Open-Cast Coal Mine Area, Inner Mongolia, China

Abstract: Abstract:In order to better understand the role of coal gangue in potential environmental and ecological risks, the leaching behavior of trace elements from coal gangue has been investigated in an open-cast coal mine, Inner Mongolia, China. Four comparative column leaching experiments were conducted to investigate the impacts of leaching time, pH values and sample amount on the leaching behavior of trace elements. Enrichment factors (EF), maximum leached amount (L am ), maximum leachability (L rm ), effects ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Meanwhile, the content of Ga, Se, As, and Sn are much higher in the Huainan Coalfield coal gangue compared with the Clarke values, while the content of other trace elements are lower [38]. The coal gangue in the Wulantuga open-cast coal mine area is enriched in Co and depleted in Se, Cd, and Hg, and the other trace elements are close to the concentrations of the world Clarke values [37].…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Meanwhile, the content of Ga, Se, As, and Sn are much higher in the Huainan Coalfield coal gangue compared with the Clarke values, while the content of other trace elements are lower [38]. The coal gangue in the Wulantuga open-cast coal mine area is enriched in Co and depleted in Se, Cd, and Hg, and the other trace elements are close to the concentrations of the world Clarke values [37].…”
Section: Introductionmentioning
confidence: 83%
“…Therefore, some studies about the leaching behavior of trace elements from coal gangue, especially from coal gangue piles, have been done by some authors [37,56]. The leaching behavior of the trace elements from coal gangue indicated that leaching is a very complex process, which might be affected by many factors.…”
Section: Leaching Methodsmentioning
confidence: 99%
See 3 more Smart Citations